A method of gathering, selecting and hierarchizing kansei words for a hierarchized kansei model. Issue 4 (7th June 2017) - Kobayashi, Masakazu; Kinumura, Takuma
ABSTRACT: Due to maturation of science and technology, companies are required to differentiate their products in terms of subjective qualities such as aesthetics and ergonomics whose evaluation depends on customer feeling i.e. kansei. To consider customer kansei in product developments, various design methods have been developed. In our previous research, we also developed a new aesthetic design support method based on a hierarchical kansei model. In these methods, SD method is widely used to measure customer kansei. SD method scores the impression which a customer receives from products using adjectives and adjective verbs named "Kansei words" as evaluation scales. Since accuracy of SD method is affected by suitability and the number of kansei words, it is important to select kansei words suitable for products and customers. In this research, we developed a new method of gathering, selecting and hierarchizing kansei words for aesthetic design methods based on a hierarchized kansei model, like our previous one. In the proposed method, candidate kansei words are gathered by using text mining software and the kansei words best suited for a design target are selected and hierarchized based on several questionnaire investigations to customers. The proposed method can be used for any design method based on a hierarchical kansei model, but combination of the proposed method and our previous one is especially effective to reduce a customer burden, since a part of questionnaire results can be reused in the process of our previous one. In the case study, the proposed method is applied to office chair design and its effectiveness is confirmed. GRAPHICAL ABSTRACT: